Note on the relationship between sustainable development and marketing in the banking sector - Pintér, Éva; Deutsch, Nikolett (Marketing & Menedzsment, 2019)
In the last decade, a lot of publications came to light, dealing with the social and environmental responsibility of firms. Contrarily, environmental awareness had developed more slowly in banks and financial institutions than in the manufacturing sector, because these institutions generally consider themselves to be a relative environmentally friendly industry. The goal of this paper is to identify the role of financial institutions in achieving sustainable development. The authors also attempt to show, why and how can this sector become the promoter of sustainability.